Management of Ala Columella Disproportion in South East Asian Noses - Yap, Eduardo (Facial Plastic Surgery, 2020)
South East Asian noses have a characteristic ala and columella disproportion and mostly manifest as hanging ala. Simultaneous correction during rhinoplasty is recommended to achieve a good aesthetic result. Since hanging ala is a common feature, a classification system is presented as a guide for surgical management. The classification is based on the frontal view showing the alar rim connecting to the columella lobule area simulating the wings of a gull in gentle flight. A mild deformity has the gull's wing in the horizontal direction. A moderate deformity has the gull's wing in a slight inferior direction. A severe hanging deformity has the gull's wing in the inferior direction, ending below the columella lobule area, and this is mostly accompanied by retracted columella. There are various techniques for the surgical correction of hanging ala. The author has made a modification of the internal approach called “sail excision” using the groove within the lateral nasal vestibule as a landmark. The author terms this area as the vestibular groove. Sail excision involves removal of a triangular portion of tissue anterior to this vestibular groove. Another aesthetic deformity noticed in South East Asian noses is that the alar rim base is lower than the columellar base. In correcting hanging ala with involvement of the alar rim base, the sail excision is extended posteriorly following the vestibular groove as its guide to the amount to be excised. To enhance the overall aesthetic outcome, the acute columella labial angle seen in South East Asian noses has to be made fuller through surgery. This is accomplished using septal extension graft for tip projection, with preservation of the posterior angle of the caudal septum. Plumping grafts are used as filler material in the premaxillary area.
Keywords: South East Asian nose; hanging ala; vestibular groove; sail excision; extended sail excision